2012
DOI: 10.1108/14725961211246018
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors in public‐private partnership (PPP) on infrastructure delivery in Nigeria

Abstract: Purpose -Federal and State Governments began to explore more subtle alternatives for accessing private sector resources in the delivery and operation of public facilities. The purpose of this paper is to examine the types of infrastructural projects most suitable using public-private partnership (PPP) for executions and identify the critical success factors in PPP on infrastructural projects with a view to strengthening the partnership between the public (government) and private sector. The overall goal is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(60 citation statements)
references
References 7 publications
1
59
0
Order By: Relevance
“…Identifying and estimating the risk involved in the PPP project by an experienced authority is essential for the successful implementation of the project (Chan et al, 2010;Chou et al, 2012;Jefferies et al, 2002). The main purpose is to reduce the total risk involved at every stage (Babatunde et al, 2012;Cheung et al, 2012;Hwang et al, 2013;Jacobson & Choi, 2008;Li et al, 2005;Tiong et al, 1992;Zhang, 2005).…”
Section: Csfs For Pppmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying and estimating the risk involved in the PPP project by an experienced authority is essential for the successful implementation of the project (Chan et al, 2010;Chou et al, 2012;Jefferies et al, 2002). The main purpose is to reduce the total risk involved at every stage (Babatunde et al, 2012;Cheung et al, 2012;Hwang et al, 2013;Jacobson & Choi, 2008;Li et al, 2005;Tiong et al, 1992;Zhang, 2005).…”
Section: Csfs For Pppmentioning
confidence: 99%
“…Critical success factors for PPP as identified from literatureAkintoye, Edwards, and Hardcastle (2005); Zhang and Asce (2005); Chan, Lam,Chan, Cheung, and Ke (2010);Cheung, Chan, and Kajewski (2012);Chou, Tserng, Lin, and Yeh (2012);Babatunde, Opawole, and Akinsiku (2012); Osei-kyei andChan (2015) Li et al (2005)Chan et al (2010); Abdul-Aziz and Kassim (2011);Chou et al (2012); Osei-kyei andChan (2015).…”
mentioning
confidence: 99%
“…The increasing number of PPP projects has attracted the attention of scholars in related fields [41]. The infrastructure applications of PPP mode has been investigated in several approaches, including relation governance [25], concessionaire determinants [42], contract governance [43], risk allocation [26,27], critical factors [44,45], and sustainability performance [23,24,46]. In this context, numerous scholars are concerned with the unsustainability of PTI projects, so they explore appropriate research angles and methods to ensure and improve sustainability performances [9].…”
Section: Understanding Sustainability In Pti Projectsmentioning
confidence: 99%
“…Alhumoud et al, 2010Mathew & Ramaswamy, 2010;Kippiliand & Aryasr, 2012;Gupta et al, 2013;Dahir, 2012;Mohammed et al, 2012;Babatunde et al, 2012;Emmanuel, 2014. Santoso et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammed et al suggested that the risk factors should be minimized to ensure successful implementation of BOT projects. Babatunde et al (2012) argued that a well-organized and committed public agency seem to be the most important factors to the private investors. They also found that factors such as transparency in the procurement process and shared authority between public and private sector are the CSFs that are most consequential to the public clients.…”
Section: Introductionmentioning
confidence: 99%